A Qualitative Toolkit for Institutional Research. Issue 174 (24th October 2017) - George Mwangi, Chrystal A.; Bettencourt, Genia M.
Abstract: This chapter provides tools, resources, and examples for engaging qualitative inquiry as a part of institutional research and assessment. It supports the development of individual ability and organizational intelligence in qualitative inquiry.